Итоги кольцевания рукокрылых в Украинской ССР за 1939—1967 гг. Сообщение II - Абеленцев, В.И.; Колюшев, И.И.; Крочко, Ю.И.; Татаринов, К.А. (Вестник зоологии, 1969)
The data are presented concerning 1551 individuals of Chiroptera belonging to five species out of 3875 individuals marked in the Ukraine and belonging to 14 species out of 24 registered ones. 109 individuals are met repeatedly, among them Rhinolophus hipposideros—3 individuals, Rhinolophus ferum-equinum— 28, Miniopterus schreibersi — 76, Barbastella barbastella — 2.
Maximum distances of Chiroptera migration, the duration of ring carrying and the data on dynamics of cave populations are given. Miniopterus schreibersi ringed in the Transcarpathia were met repeatedly in the Czechoslovak Socialist Republic and Hungarian People’s Republic. Miniopterus schreibersi ringed in the Hungarian People’s Re-pblic were found in the Transcarpathia. One male was met eight years after the ringing and set free again.
Rhinolophus — settled animals, they migrate in searching for the hibernation places within the radius up to 20 km.